Manajemen Pemasaran Dan Strategi Promosi Bisnis - Nedi Rinaldi (Journal of Innovative and Creativity, 2025)
This study aims to analyze marketing management practices, digital and conventional promotion strategies, as well as the challenges faced by small and medium enterprises (SMEs). The research employed a qualitative approach with a case study method, where data were collected through in-depth interviews, observations, and promotional document analysis. Data analysis was conducted using grounded theory through processes of reduction, categorization, and triangulation to ensure the validity of the findings. The results indicate that marketing management practices in SMEs remain relatively simple and intuitive, while digital promotion strategies are becoming increasingly dominant in line with technological developments. Nevertheless, conventional promotion is still maintained to preserve close relationships with local consumers. The main obstacles identified include limited digital literacy, financial constraints, and a lack of product differentiation. These findings highlight that the integration of marketing management and promotion strategies is a key factor in increasing sales, strengthening brand image, and creating sustainable competitive advantage.